Spatiotemporal evolution and driving forces of landscape ecological risk in the lower reaches of the Yellow River from 2000 to 2020 - Yu Lin; Jie Zhou; Jin Wang; Hao Xu; Yan Li; Feiyong Chen; Yaohui Liu (Scientific Reports)
Abstract Rapid urban development and human activities have led to drastic changes in land use, resulting to heightened ecological pressures and risks to ecosystems, especially in cities along the lower reaches of the Yellow River (CLRYR), China. However, the landscape pattern and associated ecological risks in the CLRYR in the past twenty years remain unclear. In this study, we employed the land use data to identify the primary landscape types and their transformations, providing an in-depth analysis of the prevailing landscape pattern and the landscape ecological risk (LER) in the CLRYR. Additionally, we explored the spatial distribution of LER and investigated the underlying driving forces behind these changes. The results reveal that: (1) Cropland is the main landscape type in the CLRYR region; however, the area of cropland decreases with the transition to impervious. (2) Due to human activities, landscape fragmentation and diversity have gradually increased in CLRYR, while aggregation has gradually decreased, until there was some improvement between 2015 and 2020. (3) The LER in the CLRYR region exhibits instability, with values of 0.1761, 0.1751, 0.1760, 0.1773, and 0.1751 displaying a fluctuating downward trend. Directional distribution analysis indicates a movement of the LER center of gravity towards the mouth of the Yellow River, accompanied by an increasing dispersion pattern. Analysis of driving forces suggests that natural factors hold greater explanatory power compared to social factors. Moreover, interaction detection results reveal that the combined effect of any two factors surpasses that of a single factor. The findings offer a theoretical foundation for enhancing planning policies aimed at striking a balance between environmental preservation and social advancement within the CLRYR region.